Failure analysis of radial bearings used in the refining of petroleum products - Kovalev Mark; Lyashenko Daniil; Kurakin Maksim; Shakhmatov Aleksey (E3S Web of Conferences, 2019)
The problem of premature failure of bearings is a common type of failure. In most cases, the destruction occurs due to violation of operating conditions. Since the destruction of bearings is a frequent occurrence, consideration of this special case of destruction in the future will help to avoid such problems. The object of research is the screw compressor bearings destroyed during operation. To identify the causes, a collapsed bearing was examined and a bearing that did not collapse during operation.